Microsoft Azure networking : the definitive guide - Valiramani, Avinash (Pearson Education Inc., 2022)
For cloud environments to operate and scale as they should, their networking components must be designed and configured well. Now, there’s a complete, best-practice guide to designing, deploying, and managing Azure networking services for maximum performance, scalability, and value. Writing for every professional involved in delivering Azure workloads and services, leading enterprise cloud consultant Avinash Valiramani shows how to make the most of Azure tools and services to reduce downtime, avoid unnecessary cost, simplify management, and maintain excellent performance no matter how large you scale. Valiramani addresses a wide spectrum of Azure tools and offerings, offering practical guidance for all stages of your Azure journey, and all environments, no matter how sophisticated. He addresses virtual networks, gateways, Azure Traffic Manager, Azure ExpressRoute, Web Application Firewall, load balancing, firewalls, Azure Bastion, Azure DNS, and more. Drawing on extensive experience in widely diverse environments, he combines hands-on knowledge and practical field advicesystematically helping you make the most of all your Azure investments.